Population-Based Evaluation of Lumbar Puncture Opening Pressures - Wang, Feng; Lesser, Elizabeth R.; Cutsforth-Gregory, Jeremy K.; Bhatti, M. Tariq; Kilgore, Khin P.; Hodge, David O.; Graff-Radford, Jonathan; Petersen, Ronald C.; Knopman, David S.; Mielke, Michelle M.; Lanzino, Giuseppe; Leavitt, Jaqueline A.; et al. (Frontiers in Neurology, 2019)
Importance: Prior studies evaluating opening pressure (OP) have mostly involved lumbar puncture (LP) for diagnosis of neurologic disease or small cohorts of healthy volunteers and therefore the normal OP is not well defined. Objective: The goal of this study was to establish the normal range of OP in a community-based population using the Mayo Clinic Study of Aging (MCSA) and to evaluate factors that contribute to OP variability. Design: LP OP were obtained from participants aged 32 to 95 years between 11/1/07 and 10/1/17, as part of routine data collection for the MCSA, a longitudinal, population-based study of residents of Olmsted County, Minnesota. Setting: A longitudinal, population-based study of residents of Olmsted County, Minnesota. Participants: There were 639 participants (56.8% male; 98.5% white) who underwent LP with recorded OP as part of the MCSA. Intervention: LP Main Outcome(s) and Measure(s): LP OP was recorded along with variables that could possibly influence its variability, including age, body mass index (BMI), and obstructive sleep apnea (OSA). Results: 639 participants (56.8% men) underwent LP with recorded OP; average age was 71.0 years (SD 10.9) with a mean BMI of 28.0 (SD 4.6). Mean OP was 155.4 mmH2O (SD 41.9) with a 95% reference interval of 82-242 mmH2O (range 60-314; Q1, Q3: 124, 182). Increasing age was associated with lower OP (p<0.001), while increasing BMI was associated with higher OP (p<0.001). Twelve (2%) participants had OP ≥250 mmH2O; they were younger (58.5 (SD 8.2), p<0.001), had higher BMI (33.6 (SD 4.6), p<0.001), and were more likely to have OSA (75%, p<0.001). Among the 79 participants with repeat LPs within 2.5 years, the coefficient of repeatability (CR) was 64.9. Ten (12.7%) had an OP difference ≥50 mmH2O between serial LPs. Conclusions and Relevance: This large population-based study showed that LP OP can vary significantly among individuals. Higher OPs were associated with higher BMI and younger age.